Allelopathic Effects on Seedlings Growth of Trigonella foenum graecum and Coriandrum sativum - Junaid Aslam2 and Vimala Yerramilli1, Mohammed Akmal1* (Journal of Phytology, 2010)
In present investigation, Allelopathic (negative interaction) effect was studied on Trigonella foenum graecum L. and Coriandrum sativum L. seedlings. Seeds of these crops were grown in combinations on its own extracts with different dilution. The seedling growth were studied in terms of radicle length, dry weight, total nitrogen and carbohydrate contents at 3rd, 5th and 7th day interval immediatly after radicle emergence. Trigonella seedlings showed growth inhibition in all dilutions of its own seed extracts up to 7th day. Likewise, Coriandrum seedlings also showed growth inhibition at all three days interval in all dilution when grown in Trigonella extract. Furthermore, Trigonella and Coriandrum seedlings exhibited growth inhibition when grown in their own seed extract. Trigonella was however, showed less growth inhibition as compared to Coriandrum when grown in coriender seed extracts. The total nitrogen and carbohydrate contents were low in both Trigonella and Coriandrum seedlings grown at the seed extracts of each comparatively to control.